Peningkatan Performa DIM Waste pada Departemen Secondary Processing PT X - Victoria, Karina; -, Felecia (Jurnal Titra, 2014)
One of the waste in the Secondary Processing Department at PT X is cigarette reject. The average of cigarette reject rate from January until February 2014 was around 2,21%, while the company target was 2,15%. This research was conducted to reduce cigarette reject rate, so that it will improve DIM waste performance. Steps to complete this research were based on DMAIC framework which was started by cigarette reject mapping, data collection of cigarette reject in each waste point, then the root cause analysis to obtain some solutions. It was found 4 waste points in the Secondary Processing Department. However, based on effort and impact diagram we only considered 3 waste points for improvement. Improvements was done by designed a cigarette shredder machine to separate tobacco from the cigarette paper, replacing machine components, updating tasklist cleaning maker, and focused on process development. As a results of the improvements at all 3 waste points, the average of cigarette reject reduced to 2,04%. This value is significantly lower than the target, which is 2.15%. While invest Rp. 13.000.000,00 for making the machine, the company might save Rp. 88.573.564,61 during the implementation period (2 months).